2023
DOI: 10.3390/jof9050547
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Genome-Based Characterization of Biocontrol Potential of Bacillus siamensis YB-1631 against Wheat Crown Rot Caused by Fusarium pseudograminearum

Abstract: Fusarium crown rot (FCR) caused by Fusarium pseudograminearum is one of the most serious soil-borne diseases of wheat. Among 58 bacterial isolates from the rhizosphere soil of winter wheat seedlings, strain YB-1631 was found to have the highest in vitro antagonism to F. pseudograminearum growth. LB cell-free culture filtrates inhibited mycelial growth and conidia germination of F. pseudograminearum by 84.14% and 92.23%, respectively. The culture filtrate caused distortion and disruption of the cells. Using a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 98 publications
(140 reference statements)
0
4
0
Order By: Relevance
“…Many Bacillus species have been observed to display fairly conserved 16S rRNA sequences compared to other genera, and the use of this taxonomic marker is sometimes insufficient to define the species [ 23 ]. For this reason, the analysis of additional housekeeping genes, such as gyrA , gyrB , and pycA , has been recently incorporated in order to obtain a more reliable phylogeny [ 24 , 25 , 26 , 27 ]. We additionally used the gyrB and pycA genes for the identification of Bacillus strains.…”
Section: Methodsmentioning
confidence: 99%
“…Many Bacillus species have been observed to display fairly conserved 16S rRNA sequences compared to other genera, and the use of this taxonomic marker is sometimes insufficient to define the species [ 23 ]. For this reason, the analysis of additional housekeeping genes, such as gyrA , gyrB , and pycA , has been recently incorporated in order to obtain a more reliable phylogeny [ 24 , 25 , 26 , 27 ]. We additionally used the gyrB and pycA genes for the identification of Bacillus strains.…”
Section: Methodsmentioning
confidence: 99%
“…It was previously reported that Bacillus velezensis YB-185 had strong inhibitory effects on Fp mycelium growth and spore germination and significantly reduced stem basal rot in wheat ( Zhang et al, 2022 ). The inhibition rate of PDA medium containing 20 and 66% of B. siamensis YB-1631 fermentation filtrate on Fp spore germination was 84.14 and 92.23%, respectively ( Dong et al, 2023 ) In the present study, the TM28 strain of T. muroii proved to be a promising antagonistic microorganism for the control of wheat FCR caused by Fp .…”
Section: Discussionmentioning
confidence: 54%
“…As reported, Trichoderma harzianum has been shown to effectively control FCR, as evidenced by Kthiri et al [13]. Additionally, Bacillus siamensis YB-1631 appears to have significant potential in promoting wheat growth and controlling wheat FCR [14]. Besides Pseudomonas fluorescens, P. putida, and P. aeruginosa in the Pseudomonas clade are important resources for developing biological control agents [15].…”
Section: Introductionmentioning
confidence: 87%